2002
DOI: 10.1007/s11745-002-1019-7
|View full text |Cite
|
Sign up to set email alerts
|

Transformations of DHEA and its metabolites by rat liver

Abstract: Because dehydroepiandrosterone (DHEA) has a wide variety of weak beneficial effects in experimental animals and humans, we searched for metabolites of this steroid in the hope of finding more active compounds that might qualify for the title "steroid hormone." Incubation of DHEA with rat liver homogenate fortified with energy-yielding substrates resulted in rapid hydroxylation at the 7alpha-position of the molecule and subsequent conversion to other 7-oxygenated steroids in the sequence DHEA --> 7alpha-hydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 47 publications
4
9
0
Order By: Relevance
“…The findings for DHEA support the recently reported model suggesting 7␣-hydroxylation of the parent steroid, reversible conversion of the product to a 7-oxointermediate, and finally conversion to the 7␤-hydroxylated metabolite [28,46].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The findings for DHEA support the recently reported model suggesting 7␣-hydroxylation of the parent steroid, reversible conversion of the product to a 7-oxointermediate, and finally conversion to the 7␤-hydroxylated metabolite [28,46].…”
Section: Discussionsupporting
confidence: 89%
“…For the 7␤-hydroxylated metabolites of Preg, the results in women also were consistent with the reported model [28,46], with both pair and partial correlations being significant. In men, a significant pair correlation was found, but an insignificant partial correlation was found between Preg7a and Preg7b, indicating the lesser importance of substrate concentration in product formation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, inhibition of state 3 respiration rate and FoF 1 ATPase activity in mitochondria by addition of DHEA and DHEA-S in vitro [29,30,31] would argue against this possibility. Alternative mechanism that has been proposed is that secondary metabolites, steroid in nature, may mediate DHEA action [32]. More recently, it has been demonstrated that DHEA is metabolized to 7α-hydroxy-DHEA and δ5-androstene-3β,17β-diol.…”
Section: Discussionmentioning
confidence: 99%
“…DHEA is readily converted metabolically to derivatives that are more active in some assays (24,30,31). In rat liver homogenate, the sequence is DHEA 3 7␣-OH-DHEA 3 7-oxo-DHEA 3 7␤-OH-DHEA 3 androst-5-en-3␤,7␤,17␤-triol.…”
Section: Other Active Components Of the Dhea Pathway Do Not Affect Thementioning
confidence: 99%